2018
DOI: 10.3892/etm.2018.7038
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of long non‑coding RNA and mRNA in children with Henoch‑Sch�nlein purpura nephritis

Abstract: Long non-coding RNAs (lncRNAs) serve an essential role in regulating immunological functions. However, their impact on Henoch-Schönlein purpura nephritis (HSPN), has remained elusive. The present study determined the expression of lncRNAs and mRNAs in the peripheral blood of 6 children with HSPN and recruited 4 healthy children for comparative study. High-throughput sequencing revealed outstanding differences in lncRNA and mRNA expression, which were verified through reverse transcription-quantitative polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…In particular, these mRNAs and proteins were ranked according to their P values (in ascending order), and the functions of the top 10 mRNAs and proteins were searched in GeneCards and UniProt databases. They mainly were found to be involved in immunity, apoptosis, platelet and coagulation, and tumor necrosis, consistent with the pathway enrichment results, and those functions were related to nephritis and renal injury [ 10 , 15 , 19 ]. It is worth noting that most proteins were differentially expressed between different types of HSPN while their corresponding mRNAs were not differentially expressed between those groups (Supplementary Table S 2 and Supplementary Table S 3 ).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In particular, these mRNAs and proteins were ranked according to their P values (in ascending order), and the functions of the top 10 mRNAs and proteins were searched in GeneCards and UniProt databases. They mainly were found to be involved in immunity, apoptosis, platelet and coagulation, and tumor necrosis, consistent with the pathway enrichment results, and those functions were related to nephritis and renal injury [ 10 , 15 , 19 ]. It is worth noting that most proteins were differentially expressed between different types of HSPN while their corresponding mRNAs were not differentially expressed between those groups (Supplementary Table S 2 and Supplementary Table S 3 ).…”
Section: Discussionsupporting
confidence: 78%
“…Of these, RPS17-201 is of most promise with it being found to be continuously downregulated throughout HSPN disease. RPS17 encodes a ribosomal protein, involved in the generation of serum IgA [ 15 ]. Furthermore, it was found that most DEGs were only differentially expressed in either early HSPN or late HSPN (Supplementary Table S 2 and Supplementary Table S 3 , respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, uc001kfc.1 (n381526, NONHSAT015462.2) has been only reported in two literatures about cholesteatoma (Gao et al, 2018) and purpura nephritis (Pang et al, 2019). According to NONCODE, this lncRNA is highly expressed in human adipose tissue and no homologues in other non-human animal models has been reported to date (Fang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%